The petrogenesis and implications of deformed late Caledonian–early Hercynian granites in the Wuyi area, South China. (23rd June 2017) - Zhao, Xilin; Jiang, Yang; Xing, Guangfu; Yu, Minggang; Liu, Kai; Chen, Zhihong; Yu, Shengyao
Abstract: Precambrian basement rocks have been affected by Caledonian thermal metamorphism. Caledonian‐aged zircon grains from Precambrian basement rocks may have resulted from thermal metamorphism. However, Hercynian ages are rarely recorded. Zircon U–Pb Sensitive High Resolution Ion Microprobe (SHRIMP) dating reveals that zircon ages from the Huyan, Lingdou, and Pengkou granitic plutons can be divided into two groups: one group with ages of 398.9 ±5.3 Ma, 399 ±5 Ma, and 410.2 ±5.4 Ma; and a second group with ages of 354 ±11 Ma, 364.6 ±6.7 Ma, and 368 ±14 Ma. The group of zircon U–Pb ages dated at 410–400 Ma represent Caledonian magmatism, whereas the 368–354 Ma ages represent the age of deformation, which produced gneissosity. The three plutons share geochemical characteristics with S‐type granites and belong to the high‐K calc‐alkaline series of peraluminous rocks. They have ( 87 Sr/ 86 Sr)i ratios of 0.710 45–0.724 68 and εNd(t) values of −7.33 to −10.74, with two‐stage Nd model ages (TDM 2 ) ranging from 1.84 Ga to 2.10 Ga. Magmatic zircon εHf(t) values range from −3.79 to −8.44, and have T DMC ages of 1.65–1.93 Ga. The data suggest that these granites formed by partial melting of Paleoproterozoic to Mesoproterozoic continental crust. A collision occurred between the Wuyi and Minyue microcontinents within the Cathaysia Block and formed S‐type granite in the southwest Fujian province. The ca 360 Ma zircon U–Pb ages can represent a newly recognized period of deformation which coincided with the formation of the unified Cathaysia Block. Abstract : A collision occurred between the microcontinents within the Cathaysia Block and formed S‐type granite in the southwest Fujian province. The ca 360 Ma zircon U–Pb ages may represent a newly recognized period of deformation which conincided with the formation of the unified Cathaysia Block. Abstract : 　先カンブリア時代の基盤岩類はカレドニア造山運動の熱変成作用を受けている.よって先カンブリア時代の基盤岩からカレドニアの年代を示すジルコンが得られた場合,  それは熱変成作用によるものの可能性がある.しかしながら, ヘルシニアン造山運動の年代は非常に稀である. SHRIMPによるジルコンのウラン鉛年代によると,  Huyan,  LingdouおよびPengkouの花崗岩体のジルコンは二つのグループに分けることができる. ひとつはカレドニアの火成活動に対応する410−400 Maの年代を示すグループで, もう一つは368−354 Maの片麻岩状組織をつくりだした変形年代を示すグループである. 上記,  三つの花崗岩体はSタイプのhigh‐Kカルクアルカリ系列の過アルミナ岩である.ストロンチウム同位体初生値は0.71045−0.72486, εNd(t)値は−7.33から−10.74であり, ネオジムの2‐ステージモデル年代は1.65−1.93 Gaを示す. 火成由来のジルコンのεHf(t)は–3.79から−8.44であり, TDMC 年代は1.65から1.93 Gaである. これらのデータは,  花崗岩体が古原生代から中原生代の大陸地殻が部分融解して生成したことを示唆している. Cathaysia岩塊内ではWuyiとMinyueマイクロ大陸の衝突が起こっており,  福建省の南西にSタイプの花崗岩を形成した. 約360 Maを示すジルコンのウラン鉛年代は,  このCathysia岩体の形成に関係する変形年代を示しているの可能性がある.